Validation of a measuring instrument for the perception of oral health in women - Campos, Juliana Alvares Duarte Bonini (2014)
The aim of this study was to estimate the reliability, validity and factorial invariance of the Portuguese version of the Geriatric/ General Oral Health Assessment Index (GOHAI) as applied to Brazilian women. A total 701 women over 18 years of age participated in this study. Telephone interviews were conducted. We evaluated the construct-related validity through factorial, convergent and discriminant validity. We carried out a confirmatory factor analysis using the χ2/df, CFI, GFI and RMSEA indexes. The invariance of the model in a second independent sample was estimated by multi-group analysis and internal consistency using Cronbach’s alpha coefficient. Items 5 and 9 presented factor weights below the adequate value and were removed. The three-dimensional and unifactorial model presented an adequate fit. We observed strong factorial invariance of the models in two independent samples (three-factor: ρλ = 0.62; pCov = 0.89, one-factor: ρλ = 0.81; pCov = 0.68) and weak factorial invariance between users and nonusers of dental prosthetics (threefactor: ρλ = 0.55; pCov = 0.01, one-factor: ρλ = 0.51; pCov = 0.02). The convergent validity was suboptimal. Internal consistency was adequate. The GOHAI applied to the study sample showed adequate reliability, factorial validity and stability in independent samples and between users and nonusers of dental prosthetics in both the threedimensional and the unifactorial structures.